Meningkatkan Kemampuan Mengenal Anggota Keluarga Melalui Media PECS (Picture Exchange Communication System) pada Anak Autisme Kelas TKLB di SLB Luak Nan Bungsu Payakumbuh - Nurlathifah Nurlathifah; Damri Damri (Universitas Negeri Padang, 2019)
This research was to found out the proceeded of increasing the ability to know family members through media Picture Exchange Communication System and to prove that media Picture exchange Communication System could improved the ability to know family members of autism children in class TKLB at Payakumbuh Luak Nan Bungsu. This study used the Single Subject Research (SSR) method. This study consisted of trhee conditions, namely the condition of the first baseline, the second intervention, and the third baseline. In this study data collection techniques used data collection by direct obsercation. The results obtained by using media Picture Exchange Communication System could improved the ability to know family members for children with autism in the class TKLB at Payakumbuh Luak Nan Bungsu.